The Role of the Village Head as an Innovator in Implementing Good Governance in Sukahurip Village, Pangandaran District, Pangandaran Regency - Selvi Octaviasari; Arie Budiawan; Neti Sunarti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract This study was motivated by the important role of the Village Head as an innovator in promoting change and improving village governance in Sukahurip Village, Pangandaran District, Pangandaran Regency. Although supported by various resources, several challenges remain in the implementation of village innovation. This study aims to examine the role of the Village Head as an innovator in village governance by employing a qualitative research method. The study involved 10 informants, and data were collected through observation, interviews, documentation, and literature review. Data analysis was conducted by systematically processing the findings from interviews and observations to draw research conclusions. The results indicate that the Village Head has performed the role of an innovator through the implementation of technology-based administrative systems, the utilization of village information media, the development of community empowerment programs, and efforts to establish more effective public services and village governance. However, the implementation of this role has not yet been fully optimized due to several constraints, including limited development of community potential-based programs, inadequate utilization of information technology, insufficient exploration of community ideas and aspirations, and limited capacity-building opportunities for village officials. These challenges are influenced by budget constraints, underutilized village potential, low levels of technological literacy, limited community participation in contributing ideas, and unequal access to training opportunities for village officials. To address these issues, the Village Head has undertaken various initiatives, including enhancing the use of information technology, expanding opportunities for community participation, developing innovative programs based on local village potential, increasing training for village officials, and conducting continuous guidance and evaluation to ensure that village governance innovation is implemented effectively, sustainably, and for the benefit of the community. Keywords: Role, Innovator, Village Head, Good Governance